Association between Thyroid-Stimulating Hormone Level after Total Thyroidectomy and Hypercholesterolemia in Female Patients with Differentiated Thyroid Cancer: A Retrospective Study - Lee, Young Ki (J Clin Med, 2019)
Less-intense TSH suppression strategies can be used for differentiated thyroid cancer (DTC) patients with a low recurrence risk, but their metabolic outcomes are not well known. We aimed to evaluate changes in the serum cholesterol levels and the risk of hypercholesterolemia according to postoperative TSH levels in 1092 female DTC patients receiving levothyroxine after total thyroidectomy. The preoperative-to-follow-up change in total cholesterol (TC) levels in the TSH level <0.03, 0.03–0.3, 0.3–2, and 2–5 mIU/L groups was −3.69 mg/dL (p = 0.006), +0.13 mg/dL (p = 0.926), +12.46 mg/dL (p < 0.001), and +16.46 mg/dL (p < 0.001), respectively. When compared with TSH levels of 0.03–0.3 mIU/L, those of 0.3–2 mIU/L were found to be associated with hypercholesterolemia (adjusted odds ratio (AOR) = 1.86 and 5.08 for TC 200–240 and ≥240 vs. <200 mg/dL) and hyper-low-density lipoprotein (LDL)-cholesterolemia (AOR = 2.76 for LDL-cholesterol ≥160 vs. <130 mg/dL). Additionally, TSH levels of 2–5 mIU/dL were associated with hypercholesterolemia (AOR = 2.85 and 6.95 for TC 200–240 and ≥240 vs. <200 mg/dL) and hyper-LDL-cholesterolemia (AOR = 2.08 and 4.17 for LDL-cholesterol 130–159 and ≥160 mg/dL vs. <130 mg/dL). In patients with normal TSH level maintenance following thyroidectomy, TC levels markedly increased, resulting in an increased hypercholesterolemia prevalence. Metabolic derangement risk due to insufficient levothyroxine replacement should be considered in the adoption of less-intense TSH suppression strategies, postoperatively, in DTC patients.